Stress out the LINEs. (2nd January 2016) - Hu, Siqi; Liang, Chen; Guo, Fei
Abstract: Occupying 17% of human genome, the mobile long interspersed element 1 (LINE-1 or L1) continues to modulate the landscape of our genome by inserting into new loci and, as a result, causing sporadic diseases. It is not surprising that human cells have evolved a battery of mechanisms to control and limit the activity of LINE-1. Our recent study unravels such a mechanism that is imposed by the stress granule pathway. This mechanism functions by sequestering the LINE-1 RNA-protein complex within the cytoplasmic stress granules and thus inhibiting the nuclear import of LINE-1 RNA and its subsequent reverse transcription and integration into cellular DNA. Conditions that promote stress granule formation, such as expression of the SAMHD1 protein, further reduce LINE-1 retrotransposition.